Abstracts of the 3rd International Electronic Conference on Diversity: Biodiversity of Animals, Plants and Microorganisms - Michael Wink (Biology and Life Sciences Forum, 2025)
The 3rd International Electronic Conference on Diversity: Biodiversity of Animals, Plants and Microorganisms (IECD 2024) was held from 15 to 17 October 2024. The conference focused on the key theme of biodiversity from a wide range of domains, especially animals and plants. The conference was in a virtual format, eliminating the need for travel and other related expenses, allowing attendees to fully immerse themselves in the conference without any logistical constraints. It aimed to foster collaboration and knowledge exchange among researchers.